Perspektif Hukum Keuangan Negara Terhadap Mekanisme Pertanggungjawaban Pengelolaan Anggaran Pendapatan dan Belanja Daerah - Susanti, Aprilia Dwi (El-Dusturie, 2022)
Abstract: Local governments carry out governance based on the authority granted by the central government. The authority to manage regional finances is part of the delegation of authority to manage the work of local governments, which is set forth in the Regional Revenue and Expenditure Budget (APBD). It is the regional obligation to compile an accountability report for the implementation of this APBD, which will be examined by the Supreme Audit Agency (BPK) and reported to the Regional People's Representative Council (DPRD). The formulation of the research problem is first: How is the accountability mechanism for the management of regional revenue and expenditure budgets (APBD) in accordance with the state finance law? Second, what is the consequence if the results of the APBD audit show state/regional financial losses? The method used is normative- investigating and reviewing various laws and regulations related to the judiciary, finance and regional budgets, as well as literature review from various books, academic works, and others. Accountability, the first closing, begins with financial statements from the books of account at the end of the fiscal year, followed by further examination by the BPK. The results of the assessment are then reported to the representative body and follow-up at the DPRD level is carried out in accordance with the authority granted by law. Second, as a trustee of an adult state treasurer, the state treasurer will compensate if the results of the study of the APBD accounting report will result in losses to the state/state finances. Keywords: State/Regional Finance; APBD Accountability; State Losses. Abstrak: Pemerintah daerah melaksanakan dan menjalankan urusan pemerintahan berdasarkan kewenangan yang diberikan pemerintah pusat. Kewenangan mengelola keuangan daerah merupakan bagian dari pelimpahan kewenaangan penyelenggaraan urusan pemerintahan daerah yang dituangkan dalam Perda Anggaran Pendapatan dan Belanja Daerah (APBD). Membuat laporan pertanggungjawaban Pelaksanaan APBD ini merupakan kewajiban daerah yang selanjutnya akan diperiksa oleh Badan Pemerika Keuangan (BPK) dan dilaporkan kepada Dewan Perwakilan Rakyat Daerah (DPRD). Rumusan masalah penelitian adalah pertama, Bagaimana mekanisme pertanggung-jawaban pengelolaan dana Anggaran Pendapatan dan Belanja Daerah (APBD) menurut hukum keuangan Negara Kedua, Konsekuensi apa yang diterima apabila hasil pemeriksaan pertanggungjawaban APBD terindikasi menimbulkan kerugian terhadap keuangan Negara/Daerah? Metode yang digunakan adalah yuridis normative, meneliti dan mengkaji berbagai peraturan perundang-undangan terkait dengan keuangan daerah dan ABPD serta studi pustaka dari berbagai buku, karya ilmiah dan lainnya. Kesimpulan pertama, pertanggungjawaban diawali dengan laporan keuangan yang dibuat bendahara pada akhir tahun masa anggaran, selanjutnya BPK melakukan pemeriksaan lebih lanjut. Hasil pemeriksaan selanjutnya dilaporkan kepada lembaga perwakilan dan tindak lanjut ditingkat DPRD ini dilakukan sesuai dengan kewenangan yang diberikan oleh Undang- undang. Kedua, Bendahara daerah selaku penerima kuasa pengelola keuangan daerah mengganti kerugian apabila hasil pemeriksaan laporan petanggungjawaban APBD menimbulkan kerugian terhadap keuangan negara/daerah.